2015
DOI: 10.1111/josh.12274
|View full text |Cite
|
Sign up to set email alerts
|

Weight‐Related Behaviors When Children Are in School Versus on Summer Breaks: Does Income Matter?

Abstract: Obesity-related risk factors were more prevalent during the summer and among lower-income youths, but the income disparity in these behaviors was not exacerbated when schools are not in session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
97
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 37 publications
9
97
1
5
Order By: Relevance
“…While using direct, valid observation methods, the authors acknowledged their inability to comment on foods consumed within the home environment. Our findings are also encouraging in light of recent National Health and Nutrition Examination Survey data, which demonstrates poorer diets (ie, more sugar and less fruit and vegetables) during summer breaks when compared to children's diets during school terms …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…While using direct, valid observation methods, the authors acknowledged their inability to comment on foods consumed within the home environment. Our findings are also encouraging in light of recent National Health and Nutrition Examination Survey data, which demonstrates poorer diets (ie, more sugar and less fruit and vegetables) during summer breaks when compared to children's diets during school terms …”
Section: Discussionsupporting
confidence: 71%
“…As well as school holiday food poverty, the quality of children's diets is also an area of concern—and these concerns are not limited to the United Kingdom. Findings from a large US study showed that children generally consumed more sugary beverages and fewer vegetables during school holidays, with findings consistent across all ages and household income levels . Limited research has attempted to deduce whether school food policies and practices are influential on children's overall eating patterns outside of the school environment …”
mentioning
confidence: 99%
“…Investigations into the causal factors associated with the accelerated weight gain and loss in CRF during summer are limited and report mixed findings [13, 18, 19]. Studies report that children are more active [19], while others report they are less active during summer compared to school [13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies report that children are more active [19], while others report they are less active during summer compared to school [13]. Studies report children have higher screen time during summer compared to school [18, 20], have less favorable diets or similar dietary intake during summer compared to school [13, 19], and sleep either the same amount [18] or slightly less [21] during summer compared to school. These studies were limited by study-design (e.g., between-subjects), definitions of “summer” (e.g., summer, winter, and holiday break data combined), obesogenic behavior assessment (e.g., self-report measures), and/or sample size (e.g., repeated measures on 14 children).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only a handful of studies have examined differences in children's obesogenic behaviors during summer versus school . One cross‐sectional study reported children were more physically active and had higher TV viewing during school holidays compared to school, with no reported dietary or sleep differences .…”
mentioning
confidence: 99%